Comparison of pre‐hospital triage training by role playing and lecture on nursing students' knowledge, attitude and performance. Issue 4 (21st April 2020) - Heidarzadeh, Hamid; Heidarzadeh, Zeinab; Azadi, Arman
Abstract: Aim: The objective of this study was to determine and compare the effectiveness of two methods of role playing and lecture on knowledge, attitude and performance of nursing' students in the context of pre‐hospital triage. Design: This was a pre‐test–posttest quasi‐experimental study. Methods: A total of 66 nursing students (third year) were assigned to two groups, the control group ( N = 23) and intervention group ( N = 23). START pre‐hospital triage was taught to two groups by using a lecture (control group) and role playing (intervention group) method. Immediately before the intervention and 4 weeks after the training, students' knowledge, attitude and practice in both groups were assessed through a questionnaire and a checklist. Data were analysed using SPSS software version 21. Results: The results showed that the mean scores of knowledge, attitude and performance increased after intervention in both groups ( p < .05). The mean ( SD ) difference of total performance score from baseline to follow‐up in the experimental group and the control group was 23.91 (13.83) and 7.00 (13.20), respectively ( p < .001). While there was no significant difference between the mean ( SD ) difference of knowledge and attitude scores in the experimental group and the control group before and after the intervention ( p > .05).